PENGARUH PEMBERIAN ISCHEMIC COMPRESSION DAN CONTRACTRELAX STRETCHING TERHADAP INTENSITAS NYERI MYOFASCIAL TRIGGER POINT SYNDROME OTOT UPPER TRAPEZIUS - Isidorus - Jehaman; Sri Masyuni Berasa; Sabirin Berampu; Timbul Siahaan; Miftahul Zannah (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Myofascial trigger point syndrome is a hypersensitive pain point in the tightened area that can cause local pain, if pressed it will give spesific, and the muscle that has the most myofascial trigger point syndrome is the upper trapezius. Purpose: This study is to find aims to determine the effect of ischemic compression and contract relax stretching on the intensity of myofascial trigger point syndrome upper trapezius muscle in Nurse station (Ns) administration employees at Granmed Lubuk Pakam Hospital in 2019. This type of research is a type of pure experimental research using one group pre and post test design research, conducted at Grandmed Lubuk Pakam hospital. The population and sample used in this study were 13 people. The statistical test of the hypothesis with the t test obtained p- value Î± < (0.001 >0,05). Ther is the effect of fiving ischemic compression and contract relax stretching to the intensity of myofascial pain trigger point syndrome upper trapezius muscle in Nurse station (Ns) administration employees in Granmed Lubuk Pakam Hospital in 2019. The researcher recommends that the next researcher add a longer sample size and research time so that the result of the research obtained are more maximal.